Estimating the Time Reproduction Number in Kupang City Indonesia, 2016–2020, and Assessing the Effects of Vaccination and Different Wolbachia Strains on Dengue Transmission Dynamics - Meksianis Z. Ndii; Lazarus Kalvein Beay; Nursanti Anggriani; Karolina N. Nukul; Bertha S. Djahi (Mathematics, 2022)
The use of a vaccine and Wolbachia bacterium have been proposed as new strategies against dengue. However, the performance of Wolbachia in reducing dengue incidence may depend on the Wolbachia strains. Therefore, in this paper, the performance of two Wolbachia strains which are WMel and WAu, in combination with the vaccine, has been assessed by using an age-dependent mathematical model. An effective reproduction number has been calculated using the Extended Kalman Filter (EKF) algorithm. The results revealed that the time reproduction number varies overtime with the highest one being around 2.75. Moreover, it has also found that use of the vaccine and Wolbachia possibly leads to dengue elimination. Furthermore, vaccination on one group only reduces dengue incidence in that group but dengue infection in the other group is still high. Furthermore, the performance of the WAu strain is better than the WMel strain in reducing dengue incidence. However, both strains can still be used for dengue elimination strategies depending on the level of loss of Wolbachia infections in both strains.